Environmental regulation and financial stability: Evidence from Chinese manufacturing firms - Huang, Bihong; Punzi, Maria Teresa; Wu, Yu (Journal of Banking & Finance, 2022)
This paper evaluates the short-run economic and financial implications of tightening the environmental regulations. We build an Environmental Dynamic Stochastic General Equilibrium (E-DSGE) model that combines green policies aiming to reduce firms’ emission together with financial frictions and endogenous default. The simulation results show that tightening environmental policies dampens the positive impact of expansionary shocks, compromises the firms’ ability to repay loans, and consequently poses risks to the financial stability. For the empirical analysis, we examine the effect of environmental regulations tightened by the Chinese 11th Five-Year Plan on manufacturing firms’ productivity and its implications for the financial sector. Using the difference-in-difference approach, we find that the manufacturing firms’ productivity deteriorated due to the enhanced environmental regulation stringency, making the profitability and total output decline accordingly. As a result, firms located in the cities with higher emission reduction targets were more likely to default, threatening the financial stability.